POLYSULFONE MEMBRANE WITH ZEOLITE FILLER FOR CO2/CH4 GAS SEPARATION: A REVIEW - Susanti, Indri (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Membrane technology for gas separation applications are limited by a